Litchi‐derived platinum group metal‐free electrocatalysts for oxygen reduction reaction and hydrogen evolution reaction in alkaline media. Issue 2 (24th March 2023) - Mirshokraee, Seyed Ariana; Muhyuddin, Mohsin; Lorenzi, Roberto; Tseberlidis, Giorgio; Vecchio, Carmelo Lo; Baglio, Vincenzo; Berretti, Enrico; Lavacchi, Alessandro; Santoro, Carlo
Abstract: Within the framework of the circular economy, the waste litchi's skins were upgraded and transformed into electrocatalysts for oxygen reduction reaction (ORR) and hydrogen evolution reaction (HER). The waste litchi's skins were pyrolyzed, activated, and then used as carbon support for fabricating metal–nitrogen–carbons (M–N–Cs) which belong to a promising class of platinum group metal‐free electrocatalysts. The activated char was functionalized with transition metal (Fe, Ni, and Co)‐ phthalocyanine (Pc) in monometallic and bimetallic fashion by subjecting it to a thermal treatment at 600 and 900°C. The samples functionalized at 900°C showed higher performance for HER due to the formation of metal nanoparticles, whereas the samples functionalized at 600°C showed higher performance for ORR. Particularly, sample Ni–Co 900 had an overpotential of −0.38 V for HER, while the sample Fe 600 was the most active electrocatalyst for ORR by demonstrating the onset potential of ∼0.9 V (a half‐wave potential of ∼0.81 V) with the least production of unwanted peroxide anion. Abstract : A strategic transformation of waste biomass into platinum group metal‐free (PMG‐free) electrocatalysts for oxygen reduction reaction (ORR) and hydrogen evolution reaction (HER) through pyrolysis. The effects of pyrolysis temperature and choice of transition metal on the electrocatalytic activity of the developed electrocatalysts were analyzed. This work contributes to the vision of circular economy in the attainment of a sustainable society.